The Code of Medical Ethics (CME) to the beginning of the '900: the principles of the first Italian CME. - Oppes, Mario (Medicina e Morale, 2003)
The Code of Medical Ethics (CME) of the Order of Medical Doctors of the Sassari province (Italy), published in 1903, represents the first example in Italy of CME. To one hundred years of distance from his promulgation, it appears interesting to appraise the principles contained in this Code and to compare them with those inserted in the following codes. Through the historical run of medical ethics, it is possible to understand the meaning that has had in determining the behaviours of the physicians in the exercise of the profession, but above all it can be discovered, the true meaning to attribute to same medical ethics. In fact, with the advent of the bioethics, we assisted to a real crisis of medical deontology that has brought even to the loss of a shared conception of its meaning within of the professional category of the physicians in the last thirty years. From the analysis of the text of the CME of Order of Sassari, the duty to get the patient's consent for every operational action is an unexpected for those times - because the shared paternalistic physician-patient relationship - and emerging factor. There is besides a repeated call to necessity to take care of all the sick with the same appointment, independently from the social class, and this assumes particular relevance if we consider that a National Heath System (capable to guarantee uniforms levels of assistance) didn't exist at the beginning of XX century. To a large extent the CME underlines the relationships between colleagues and in the articles devoted to such problematic issue particular sensibility toward the correctness between professionals - today decidedly disregarded, so much that such demand doesn't find particular underlines in the last Italian CME (1998) - is underlined. Finally, the explicit call to the respect of the deontological norms for all the physicians is meaningful, punishment the commination of disciplinary sanctions and this assumes particular relevance if we think that one hundred years ago the Orders of Doctors had not gotten the juridical recognition, that will arrive in 1910 only yet.